A Comparative Study of Machine Learning Models for Sentiment Analysis of Dana App Reviews - Sujana, Yudianto (IJIE (Indonesian Journal of Informatics Education), 2023)
Sentiment analysis of user reviews has become increasingly important for mobile app developers, as it can provide valuable insights into customer satisfaction and guide the improvement of app features. In this study, we compared the performance of three machine learning models - Support Vector Machine, Neural Network, and Bidirectional Long Short-Term Memory - in classifying the sentiment of user reviews for the Dana mobile application. Our results showed that the Bi-LSTM model outperformed the other models, achieving the highest accuracy, precision, recall, and F1-score. The superior performance of the Bi-LSTM model can be attributed to its ability to capture long-term dependencies and contextual information within the review text, which is crucial for accurate sentiment analysis. These findings highlight the effectiveness of deep learning techniques in handling the complexities of language and sentiment analysis, particularly in the context of user-generated content. The insights from this study can inform the development of more accurate and efficient sentiment analysis tools for mobile app reviews, ultimately benefiting both app developers and users.